(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with questions of language cliché functioning in the context of stylistic and linguistic problematics, the peculiarities of functioning of stereotype units in different functional and stylistic types of the Ukrainian language are being considered in particular.